Xenocentrism as a purchase driver in viral marketing Barbie X ESQA cosmetics - Wijaya, Diorra Calysta; Boer, Rino Febrianno (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
The success of the viral Barbie movie in 2023 prompted various brands, both global and local, including ESQA Cosmetics from Indonesia, to participate in collaborative marketing campaigns. The campaign demonstrated increasing consumer engagement with pop culture trends and was reflected in consumer discussions about the Barbie X ESQA collaboration. This study focuses on analyzing consumer views on the collaboration, identifying elements that drive consumers to spread information about the product, and examining purchasing motivations by employing relevant communication theories. Using qualitative methods and netnography, data was obtained through in-depth interviews, digital observations, and linked documentation. The results show that ESQA Cosmetics strategically optimized digital marketing communications (DMC), which focused on three main interaction models: Business to Consumer (B2C), Consumer to Business (C2B), and Consumer to Consumer (C2C). These models are facilitated through social media platforms such as Instagram and TikTok, where consumers interact with promotional content and share their personal experiences. The informants in this study were influenced by the nostalgic bond with the Barbie figure, which encouraged them to engage in product discussions and participate in viral content trends. Purchasing patterns among informants reflected varying levels of consumer needs: social needs were fulfilled through interaction with peers and participation in trending discussions; ego needs were addressed through public expression of self-image; and self-actualization was reflected in creative makeup expressions using Barbie-themed cosmetics. This study concluded that xenocentrism operationalized as consumer preference for products with foreign cultural elements plays a significant role in consumer preferences, where brands associated with global icons such as Barbie can enhance product appeal. The findings demonstrate how integrated marketing strategies based on cultural resonance and nostalgia have a strong influence on consumer purchasing decisions.